Optical coherence tomography for detection of asymptomatic optic nerve lesions in clinically isolated syndrome. (11th August 2020) - Outteryck, Olivier; Lopes, Renaud; Drumez, Élodie; Labreuche, Julien; Lannoy, Julien; Hadhoum, Nawal; Boucher, Julie; Vermersch, Patrick; Zedet, Mickaël; Pruvo, Jean-Pierre; Zéphir, Hélène; Leclerc, Xavier
Abstract : Objective: To evaluate the ability of intereye retinal thickness difference (IETD) measured by optical coherence tomography (OCT) to detect asymptomatic optic nerve involvement in clinically isolated syndrome (CIS). Methods: We conducted a cross-sectional study of patients who recently presented a CIS (⩽4.5 months). All patients underwent OCT and brain/optic nerve MRI. Optic nerve involvement was defined clinically (episode of optic neuritis [ON] or not) and radiologically (optic nerve hypersignal on 3D double inversion recovery [3D-DIR]). We evaluated the sensitivity and specificity of previously published IETD thresholds and report the observed optimal thresholds for identifying symptomatic optic nerve involvement but also for identifying asymptomatic optic nerve involvement (optic nerve hypersignal without ON history). Primary outcomes were ganglion cell–inner plexiform layer (GC-IPL) and peripapillary retinal nerve fiber layer IETD. Results: The study group consisted of 130 patients. In the CIS with ON group, 3D-DIR showed a hypersignal in all 41 symptomatic optic nerves and in 11 asymptomatic optic nerves. In the CIS without ON group, 3D-DIR showed a unilateral optic nerve hypersignal in 22 patients and a bilateral optic nerve hypersignal in 7 patients. For the detection of symptomatic and asymptomatic optic nerve lesion, GC-IPL IETD had better performance. We found an optimal GC-IPL IETD threshold ≥2.83 µm (sensitivity 88.2, specificity 83.3%) for the detection of symptomatic lesions and an optimal GC-IPL IETD ≥1.42 µm (sensitivity 89.3%, specificity 72.6%) for the detection of asymptomatic lesions. Conclusions: Detection of asymptomatic optic nerve lesions in CIS requires lower IETD thresholds than previously reported. GC-IPL IETD represents an alternative biomarker to MRI for the detection of asymptomatic optic nerve lesions. Classification of evidence: This study provides Class I evidence that OCT accurately identifies asymptomatic optic nerve involvement in patients with CIS.